Bumblebee attraction to Matthiola livida flowers is altered by combined water stress and insect herbivory. Issue 8 (26th June 2022) - Salman, Ibrahim N. A.; Cna'ani, Alon; Tzin, Vered; Seifan, Merav
Abstract: Floral volatiles are among the well‐known cues that mediate plant‐pollinator interactions. Understanding plant‐pollinator interactions is especially important in arid regions, where the low abundance of pollinators limits their visiting frequency and, thus, constraints the reproductive success of many plant species. Moreover, plants in such arid habitats are exposed to abiotic stress, particularly to water shortage. Plants in arid habitats are also prone to suffer from multiple stress factors, such as the addition of pathogen and herbivore attacks. All these stress factors induce disruptions in the plant metabolism and increase physiological costs that may lead to changes in floral volatiles, thus affecting the communication between the plant and its pollinators, consequently intensifying the constraints on the plants' reproductive success. To explore this general hypothesis, we used as a model Matthiola livida (Delile) DC. (Brassicaceae), a common native plant species in arid regions of the Middle East. We first tested whether water shortage and insect herbivory, inflicted by whiteflies, Bemisia tabaci (Gennadius) (Hemiptera: Aleyrodidae), caused stress in M. livida, based on the change in carbohydrates and starch content, and examined whether the plants produced distinct volatile composition in response to these stressors. Then, we tested whether bumblebees, Bombus terrestris (L.) (Hymenoptera: Apidae), common pollinators of M. livida, were able to differentiate between plants suffering from water shortage and insect herbivory based only on volatile emission. We found that both water shortage and insect herbivory caused stress in the plants. We also found that the plants produced a distinct volatile composition in relation to the specific stress they were exposed to. Specifically, in comparison to control plants, insect herbivory increased the amounts of volatile alkanes, aldehydes, and alcohols, and reduced the amounts of esters, benzenoids, and phenylpropanoids. Water shortage reduced the amount of aldehyde volatiles and increased the amount of alcohol volatiles. Moreover, using choice experiments, we found that bumblebees differentiated between stressed and non‐stressed plants based on their volatile compositions, and preferred less stressed ones. Our study indicated that pollinators may use floral volatiles in their foraging decisions and are highly sensitive to variation in the plant conditions. This suggests that volatile cues may create a constraint on the ability of the plants to secure their reproductive success in arid habitats, that are added to the direct stress created by the arid conditions themselves. Abstract : We tested whether water shortage and insect herbivory, inflicted by whiteflies, Bemisia tabaci (Hemiptera: Aleyrodidae), caused stress in Matthiola livida (Brassicaceae), and examined whether the plants produced a distinct volatile composition in response to these stressors. Then, we tested whether bumblebees, Bombus terrestris (Hymenoptera: Apidae), common pollinators of M. livida, were able to differentiate between plants suffering from water shortage and insect herbivory based only on volatile emission. The pollinators consistently preferred the less‐stressed flowers.